(untitled) (GAIMS Journal of Medical Sciences, 2024)
Background: Evaluation of students’ performance forms one of the most important aspects in delivery of curriculum. Formative assessment & summative assessment both are widely practiced all across globe. The current study tries to establish effectiveness of formative assessment to predict outcomes in summative examination. Materials and Methods: This study employs retrospective observational study using the academic records of the first year students in Bachelor of Dental Surgery (BDS) course. The data was subjected to correlation studies applying Pearson’s correlation coefficient. Results: There is a strong positive correlation between performance in formative assessment and summative assessment for theory examination, whereas there is a moderate positive correlation between performance in formative assessment and summative assessment for practical examination. Conclusions: The internal examinations are having a moderate to strong positive correlation in predicting results of final examination; but it may not be consistent. The purpose of formative assessment is served in existent academic set-up.